1980
DOI: 10.1177/28.12.6785343
|View full text |Cite
|
Sign up to set email alerts
|

A neurochemical and immunocytochemical study of P2 protein in human and bovine nervous systems.

Abstract: The anatomical distribution of P2 protein was studied in human autopsy tissue. Spinal cord (SC) and peripheral nerve (PN) were stained by the peroxidase-antiperoxidase method with antisera to bovine P2, glial fibrillary acidic protein, and myelin basic protein (BP). P2 antiserum did not stain all of the myelin in the PN. The staining was randomly distributed and discontinuous along a given myelinated axon. P2 antiserum also stained SC myelin in a pattern similar to the PN. Only a fraction of the sheaths staine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Uyemura et al (1977) similarly noted that concentrated rabbit brain extracts reacted with anti-P, serum in an immunodiffusion reaction. Eylar et al (1980) and DeArmond et al (1980) found no immunocytochemical staining in cerebral hemispheres by use of antiserum to P, pro- tein, suggesting that the high-molecular-weight protein may be located within the brain stem. Greenfield et al (1980) and Milek et al (1981) have previously demonstrated by electrophoretic and immunochemical techniques that the small basic protein (14K) in mouse and rat PNS myelin is related to MBP rather than to P, protein.…”
Section: Discussionmentioning
confidence: 98%
“…Uyemura et al (1977) similarly noted that concentrated rabbit brain extracts reacted with anti-P, serum in an immunodiffusion reaction. Eylar et al (1980) and DeArmond et al (1980) found no immunocytochemical staining in cerebral hemispheres by use of antiserum to P, pro- tein, suggesting that the high-molecular-weight protein may be located within the brain stem. Greenfield et al (1980) and Milek et al (1981) have previously demonstrated by electrophoretic and immunochemical techniques that the small basic protein (14K) in mouse and rat PNS myelin is related to MBP rather than to P, protein.…”
Section: Discussionmentioning
confidence: 98%
“…In these studies, P2 protein was not de-tected in myelin from more rostral regions of the central nervous system (CNS), such as the cerebral cortex. P2 protein has been detected immunocytochemically in human spinal cord myelin (DeArmond et al, 1980). As in the rat and human PNS, not all of the myelin sheaths within the human spinal cord were stained by Pz antiserum.…”
mentioning
confidence: 91%
“…Immunocytochemical studies describing the distribution of myelin proteins in rat peripheral nerves demonstrated that Pz antiserum did not stain all of the myelin sheaths present (Trapp et al, 19790). Similarly, P2 antiserum did not stain all myelin sheaths in human peripheral nerves (Trapp et al, 19796;DeArmond et al, 1980;Schober et al, 1981). Although it has been claimed that Pz protein is unique to PNS myelin, biochemical and immunochemical evidence for its presence in bovine (London, 1971; Eylar and Hashim, 1974;Uyemura et al, 1977;Deibler et al, 1978;DeArmond et al, 1980), rabbit (Uyemura et al, 1977), and human spinal cord myelin (DeArmond et a]., 1980; Uyemura et al, 1977) has been reported.…”
mentioning
confidence: 99%
“…Peripheral myelin protein 2 (P2) constitutes up to 15% of total protein of peripheral nervous system (PNS) myelin [2]. P2 is also present in small amounts in central nervous system (CNS) myelin, being abundant in spinal cord and brain stem myelin [3][5]. The amount of P2, however, varies between different species, different regions of the nervous system and from fiber to fiber [6].…”
Section: Introductionmentioning
confidence: 99%